ANALISIS DRAFT UU KESETARAAN GENDER MENURUT PERSPEKTIF HUKUM ISLAM - Muhammad Baskara Tri Nugraha; Zeni Lutfiyah (Universitas Sebelas Maret, 2014)
Plan Law Justice and Gender Equality (Bill KKG) are now discussed openly in the House of Representatives. Voice pro-cons start popping up. We as Muslims have a choice whether to accept or reject the bill KKG. If the draft bill revising the Muslims should reject the draft bill. Because, fundamentally different concepts in the bill was contrary to the concepts of Islamic precepts. There are a number of reasons that we require - as a Muslim and as an Indonesian - KKG reject this bill.